PENDAPATAN DAN KELAYAKAN USAHATANI BAWANG MERAH - fattah, Muhammad Arifin; Mardiyati, Sri; Firmansyah, Firmansyah (Universitas Muhammadiyah Makassar, 2022)
Shallots are horticulture crops that are derived from vegetable commodities that have been intensively farmed for a long period by farmers. This commodity is a source of income and job opportunities that makes a significant contribution to regional economic growth. Shallots are a profitable item to cultivate because of their high demand and requirement for consumption. The goal of this research was to determine the profitability and viability of onion cultivation in Tangru Village, Malua District, Enrekang Regency. Tangru Village, Malua District, Enrekang Regency was the site of this study. The population of this study consisted of 319 shallot farmers. In this study, the number of samples was 10% of the overall population, or 31 farmers. Simple random sampling was used to collect samples from farmers.Data collection techniques used in this study were observation, interviews, and documentation. The types of data in this study are qualitative data and quantitative data. Data sources are primary and secondary data. The data analysis method used in this research is descriptive quantitative. The results of this study indicate that the average income received by shallot farmers in Tangru Village, Malua District, Enrekang Regency is Rp. 78.482.900.00/MT. Shallot farming carried out by shallot farmers is feasible.